Use of Molecular Assays and Circulating Tumor DNA in Early-Stage Colorectal Cancer: A Roundtable Discussion of the Gastrointestinal Cancer Therapy Expert Group. (28th March 2021) - Loaiza-Bonilla, Arturo; Benson, Al B.; Grothey, Axel; Karimi, Misagh; Klempner, Samuel J.; Lin, Daniel; Mahtani, Reshma; Soares, Heloisa P.
Abstract : : The use of genomic testing is rapidly emerging as an important clinical tool both for cancer diagnosis and for guiding treatment decisions in a wide range of malignancies, including gastrointestinal (GI) cancers such as colorectal cancer (CRC). Advances in technologies such as polymerase chain reaction and next-generation sequencing methods have made it possible to noninvasively screen for CRC through, for example, the use of blood- or stool-based testing, with high specificity. Tests are also available that can provide prognostic information beyond traditional clinicopathologic factors such as tumor size, grade, and nodal status, which can enable clinicians to more accurately risk stratify patients for recurrence. Lastly, in the setting of resected CRC, tests are now available that can detect circulating tumor DNA as a means for noninvasive minimal/molecular residual disease monitoring, thereby potentially guiding the use of adjuvant chemotherapy and/or escalating or de-escalating therapy. The Gastrointestinal Cancer Therapy Expert Group (GICTEG) recently convened a virtual meeting to discuss current issues related to genomic testing in GI cancer, with the goal of providing guidance on the use of these tests for the practicing community oncologist, for whom GI cancer may be only one of many tumor types encountered. This article provides a summary of the discussion and highlights the key opinions of the GICTEG on this topic. Implications for Practice: The Gastrointestinal Cancer Therapy Expert Group seeks to provide practical guidance and opinion on the treatment of gastrointestinal malignancies, including colorectal cancer (CRC), for the practicing community oncologist in situations for which guidelines from established bodies, such as the National Comprehensive Cancer Network and the American Society of Clinical Oncology, may be less clear. In the present report, clinical guidance on the use of molecular assays for a range of clinical indications in CRC is presented, including the use of circulating tumor DNA to detect minimal/molecular residual disease in patients with successfully resected early-stage CRC. Abstract : The Gastrointestinal Cancer Therapy Expert Group (GICTEG) recently convened a virtual meeting to discuss current issues related to genomic testing in gastrointestinal cancer, with the goal of providing guidance on the use of these tests for the practicing community oncologist. This article provides a summary of the discussion and highlights the key opinions of the GICTEG on this topic.